2023
DOI: 10.1177/00219983231155013
|View full text |Cite
|
Sign up to set email alerts
|

Jute-basalt reinforced epoxy hybrid composites for lightweight structural automotive applications

Abstract: The utilization of lightweight construction is one of the keys to increase the fuel efficiency and reduce the environmental effect of automobiles. Natural fiber composites are replacing expensive synthetic fibers increasingly commonly in the automotive sector. To further lower the weight and price of the vehicle without losing rigidity and strength, basalt (B) fiber could be incorporated into jute (J) fiber composites. For the generation of hybrid composite laminates, woven textiles made of J-fiber and B-fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…It is worth noting that the modulus of toughness is the ability of a material to absorb energy in plastic deformation. It is defined as the amount of strain energy density (strain on a unit volume of material) that a given material can absorb before it fractures, which can be calculated as the area under the curve up to the break as follows: 49,51,62,76,77 where ɛ 𝑓 signifies the failure strain.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the modulus of toughness is the ability of a material to absorb energy in plastic deformation. It is defined as the amount of strain energy density (strain on a unit volume of material) that a given material can absorb before it fractures, which can be calculated as the area under the curve up to the break as follows: 49,51,62,76,77 where ɛ 𝑓 signifies the failure strain.…”
Section: Methodsmentioning
confidence: 99%
“…Two perpendicular strain gauges were involved on the contrasting surfaces of each test specimen to determine the actual tensile modulus (Eact.) and the Poisson’s ratio (v12). Strain gauges were used by many authors 49,74,7881 to determine the actual tensile modulus (Eact.) and the Poisson’s ratio (v12). Strain gauges working principle is simple: the electrical resistance of a conducting wire is a function of the material’s electrical resistivity, cross-sectional area, and length.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its simplicity, low cost, and few infrastructure requirements, the wet-wrapping method was used to manufacture GFRE circular composite tubes reinforced with different wt.% of HNTs. 5,48,49 The manufacturing steps carried out at room temperature (25 ° C) can be described as follows: The mixture, consisting of epoxy/HNTs/hardener was regularly placed on the glass fabric, as shown in Figure 4(a). Glass fabric was impregnated using both a roller and a brush, Figure 4(b).…”
Section: Methodsmentioning
confidence: 99%
“…The hybrid composites developed with the combination of natural and synthetic fibers shows enhanced wear resistance and can be used in tribological applications such as sliding elements, sliding bearings, seals, conveyors, clutches, tyres brakes, etc. Jute-basalt reinforced epoxy hybrid composites for lightweight structural automotive applications was developed and assessed by Hassan Alshahrani et al 38 where it was found that hybridizing Jute fiber with Basalt fiber improved the tensile, bending, in-plane shear, and bearing characteristics of the prepared composite. Evaluation of mechanical properties of jute/glass/carbon fibers reinforced hybrid composites was carried out by Abd El-baky 39 where the results showed that the hybridization process can potentially improve the tensile and flexural properties of jute reinforced composite.…”
Section: Introductionmentioning
confidence: 99%